Challenges of IEEE 802.11a technology and improving its performance using diversity technique - Najat Shyaa Jasim Mohammed; Buraq Abdulhadi Awad; Zainab B. Abdullah; Salam W. Shneen (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
In this technology, information can be transmitted through the air without the need for cables, wires, or other electronic connectors, using electromagnetic waves such as infrared, radio and satellite frequencies. In this research, the most important challenges and problems faced by wireless communication systems were identified and how to solve and address them. (IEEE 802.11aWLAN) was also simulated and tested using Mat lab program, where the signal generated in (IEEE 802.11aWLAN) was examined in the form of orthogonal frequency division multiplexing (OFDM) modulation by examining the performance of the bit error rate of this system using diversity technology to improve the performance of this system where we adopted the reception diversity technology, In the case of line of sight (LOS) channel and multipath channel using maximal ratio combining (MRC) method. We notice that the use of the MRC receiving diversity technique in the system reduces the bit error rate and increases the efficiency of the system and the performance improve with increase the number of receiving antenna with gain 6 dB.